Synthesis, Optical, and Geometrical Approaches of New Natural Fatty Acids’ Esters/Schiff Base Liquid Crystals - Alnoman, Rua (Molecules, 2019)
Schiff base liquid crystals, known as [4-(hexyloxy)phenylimino)methyl]phenyl palmitate (IA), [4-(hexyloxy)phenylimino)methyl]phenyl oleate (IIA) and [4-(hexyloxy)phenylimino)methyl]phenyl linoleate (IIIA), were synthesized from palmitic, oleic, and linoleic natural fatty acids. The prepared compounds have been investigated for their thermal and optical behavior as well as phase formation using differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Molecular structures of all studied compounds were confirmed via elemental analysis, FT-IR, (1)H NMR, and (13)C NMR. Smectic phase is the observed mesophase for all compounds; however, their type and range depend upon the terminal alkanoate chains attached to the phenyl ring. Computational calculations, Density functional theory (DFT), energy difference of the frontier molecular orbital (FMOs), as well as the thermodynamic parameters of different molecular configurations isomers were discussed. It was found that the mesophase behavior and the geometrical characteristics were affected by the degree of unsaturation of fatty terminal chains. Furthermore, the geometrical structure of the CH=N linkage plays an important role in the thermal stability and optical transition temperature.